5*0-(2*0+4-0)=

Simple and best practice solution for 5*0-(2*0+4-0)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5*0-(2*0+4-0)= equation:


Simplifying
5 * 0 + -1(2 * 0 + 4 + 0) = 0

Multiply 5 * 0
0 + -1(2 * 0 + 4 + 0) = 0

Anything times zero is zero.
0 + -1(2 * 0 + 4 + 0) = 0

Multiply 2 * 0
0 + -1(0 + 4 + 0) = 0

Anything times zero is zero.
0 + -1(0 + 4 + 0) = 0

Combine like terms: 0 + 4 = 4
0 + -1(4 + 0) = 0

Combine like terms: 4 + 0 = 4
0 + -1(4) = 0

Multiply -1 * 4
0 + -4 = 0

Combine like terms: 0 + -4 = -4
-4 = 0

Solving
-4 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 16.7d=-3d+2 | | 4x-3y=5findy | | 4y=3y+33 | | 20-5s+4=-s-20 | | (90-x)=5x | | m^2+mn-56n^2=0 | | 5x=(90-x) | | -3n=29 | | -6g+20=-10g | | 43=-9-14x | | 12x+5=149 | | 10y-8y-y=0 | | x^2+8x=2x^2-40 | | .4x+4=40 | | 20-8=x/3 | | 1800+450=600p+1200 | | 5(x+4)+2=5x+2 | | (x^2-4x+16)(x+4)=0 | | 43=-9-14r | | 25x+16=40x | | 38.72+23.19+n=31.18 | | 22x-6-16x+4=18x-8-12x+15 | | 5y-26=-6(y+8) | | -2-10y+11y=-4 | | 17=-1-9a | | 4-0.7(p-3)=0.2(4p-3) | | 15+4x=5x+5 | | -9+x=.875x-23 | | -4x-4x=46-6 | | X^2+8x=2x^2+2x-40 | | X^12=9 | | yx+6x=7 |

Equations solver categories